2004
DOI: 10.1007/s00436-003-1063-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of toltrazuril and ponazuril on the fine structure and multiplication of tachyzoites of the NC-1 strain of Neospora caninum (a synonym of Hammondia heydorni) in cell cultures

Abstract: Rhesus monkey kidney cell cultures were used to propagate tachyzoites of the NC-1 strain of Neospora caninum (syn. Hammondia heydorni). The infected cell cultures were incubated for 4-12 h in media containing 0, 1, 10 or 100 microg/ml of either toltrazuril or ponazuril. The effects were studied by light and electron microscopy. Drug dosages of at least 30 microg/ml were needed to eliminate the parasites. Ponazuril was found (with respect to the reduction of the number of parasites) to be less effective at dosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 13 publications
2
25
0
1
Order By: Relevance
“…Other effects included distortion of the PVM, and degradation of the granular matrix of the parasitophorous vacuole. The effects appeared similar for all three drugs, and massive vacuolization of the cytoplasm of N. caninum and T. gondii tachyzoites was reported earlier also upon treatment of N. caninum-and T. gondii-infected cells with ponazuril (Darius et al 2004 ;Mitchel et al 2005). Darius et al (2004) also indicated that ponazuril was targeting the N. caninum apicoplast.…”
Section: Discussionsupporting
confidence: 81%
“…Other effects included distortion of the PVM, and degradation of the granular matrix of the parasitophorous vacuole. The effects appeared similar for all three drugs, and massive vacuolization of the cytoplasm of N. caninum and T. gondii tachyzoites was reported earlier also upon treatment of N. caninum-and T. gondii-infected cells with ponazuril (Darius et al 2004 ;Mitchel et al 2005). Darius et al (2004) also indicated that ponazuril was targeting the N. caninum apicoplast.…”
Section: Discussionsupporting
confidence: 81%
“…In previous studies, although TZR has been shown to be effective in vivo against Eimeria species and in vitro against Toxoplasma gondii (Chapman, 1987;Ricketts and Pfefferkorn, 1993), TZR-SO 2 also has a potent and broad spectrum anticoccidial activity (Lindsay et al, 2000;Gottstein et al, 2001;Franklin et al, 2003). In one of the recent studies, TZR at 10 μg/mL and TZR-SO 2 at 30 μg/mL also led to a significant reduction in the multiplication rate of N. caninum (Darius et al, 2004). Mitchell et al (2005) reported that TZR-SO 2 at 5 μg/mL inhibited development of N. caninum after approximately 48 h post exposure in African green monkey kidney cell culture.…”
Section: Resultsmentioning
confidence: 94%
“…However, interesting experimental studies that may result in an option for chemotherapeutic control at a later stage have been conducted. An effect of toltrazuril and its derivative ponazuril on tachyzoites of N. caninum has been shown in vitro (104) and in vivo in calves (200,255). In calves treated with ponazuril, the parasite was no longer detectable in the brain and other organs (255).…”
Section: Control Measuresmentioning
confidence: 99%